Familial pancreatic adenocarcinoma: association with diabetes and early molecular diagnosis. Issue 5 (May 1995) - Evans, J P; Burke, W; Chen, R; Bennett, R L; Schmidt, R A; Dellinger, E P; Kimmey, M; Crispin, D; Brentnall, T A; Byrd, D R
Abstract : We report a large pedigree in which pancreatic cancer is inherited in an autosomal dominant fashion. Diabetes and exocrine insufficiency was observed in all family members who eventually developed pancreatic cancer. The presence of diabetes, often years before the diagnosis of cancer, allowed identification of those people who had inherited the predisposing allele and who were thus at high risk for the development of malignancy. This family shows that genetic factors can have a striking effect on the development of pancreatic malignancy and diabetes mellitus. Moreover, preclinical diagnosis of pancreatic cancer in family members provided a unique opportunity to study early molecular changes that accompany the development of human pancreatic cancer. Finally, the molecular approach applied here to the early diagnosis of pancreatic cancer may prove valuable in this family for identification of subjects at risk.